The GCRO barometer 2014 - Mushongera, Darlington (My University, 2015)
The GCRO Barometer 2014 depicts developmental progress in the Gauteng City-Region (GCR) in a single interactive graphic using 38 indicators across ten key sectors. It serves as a tracking and diagnostic tool to inform policy makers and the public on where development progress is being made, and areas of concern. It also serves as a tool for benchmarking Gauteng against other South African provinces and similar sized city-regions across the world. The GCRO Barometer 2014 is the first release and shows progress in 2012 against three base years: 2002, 2007 and 2011. Overall, the Barometer shows that the developmental outlook for Gauteng is positive with significant progress realised between 2002 and 2012 in nearly all sectors. For instance, the poverty rate has fallen dramatically since 2002 and access to basic services has improved. However, there are challenges in areas such as Social Cohesion, Governance, the Labour Market and Sustainability. Sadly, people’s perceptions of government, as well as their unwillingness to participate in governance matters do not correspond to the achievements made by government during this period. This should be a cause for concern for policy makers in all spheres of government as it reflects dissatisfaction with the nature and quality of services being provided as well as the methods of provision. The Barometer also shows that the impact of government programmes is minimal over shorter time spans – change between 2002 and 2012 is considerable, but change between 2011 and 2012 is insignificant. This is a cause for concern given the 5-year cycle of electoral terms for local government in South Africa. The Barometer’s outcomes underscore the need for government to step up policy and programme monitoring with a view to achieving immediate and positive short-term impacts on communities.
Keywords: GCRO Barometer, developmental progress in Gauteng City Region